2022
DOI: 10.1007/s00167-022-07219-5
|View full text |Cite
|
Sign up to set email alerts
|

Bone–patellar tendon–bone autograft and female sex are associated with the presence of cyclops lesions and syndrome after anterior cruciate ligament reconstruction

Abstract: PurposeAssociated risk factors for the development of cyclops lesions have been little. Investigated, because most previous studies have limited their research to cases with symptomatic cyclops lesions (cyclops syndrome). The purpose of this study was to evaluate the presence of cyclops lesions using magnetic resonance image (MRI) at 6 and 12 months after anterior cruciate ligament reconstruction (ACL‐R), and to investigate the associated risk factors of cyclops lesions and syndrome. MethodsA retrospective ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Tomihara et al reported an incidence of 4.4% for symptomatic cyclops lesions. Additionally, they found a higher risk for cyclops lesions in patients with a BPTB graft compared with a hamstring graft, female patients and patients with a higher BMI [34]. Recent studies concluded an incidence of 6.7%–7.2% in different graft types [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Tomihara et al reported an incidence of 4.4% for symptomatic cyclops lesions. Additionally, they found a higher risk for cyclops lesions in patients with a BPTB graft compared with a hamstring graft, female patients and patients with a higher BMI [34]. Recent studies concluded an incidence of 6.7%–7.2% in different graft types [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…In more recent years there have been questions as to whether particular graft selection leads to a higher incidence of cyclops lesions and syndrome following ACLR. Studies have demonstrated that bone patellar bone autograft compared to hamstring autograft as well as female sex and increased BMI leads to increased rates of cyclops syndrome [16]. Quadriceps tendon autograft is becoming a popular choice of graft selection among surgeons as it shows similar biomechanical outcomes as well as improved cosmesis in comparison to other graft selections.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the use of hamstring or patellar graft does not constitute a risk factor in the development of cyclops lesion. However, there are also studies reporting that bone-tendon-bone graft is a risk factor[ 2 , 5 ]. In fact, the list of risk factors is long and most of time it is difficult to say which factors caused it in a case report.…”
Section: Introductionmentioning
confidence: 99%